2018
DOI: 10.1002/adfm.201803200
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Graphene Oxide Films with Au and MoOx Nanoparticles as Efficient p‐Contact Electrodes for Inverted Planar Perovskite Solar Cells

Abstract: A graphene oxide (GO) film is functionalized with metal (Au) and metaloxide (MoO x ) nanoparticles (NPs) as a hole-extraction layer for highperformance inverted planar-heterojunction perovskite solar cells (PSCs). These NPs can increase the work function of GO, which is confirmed with X-ray photoelectron spectra, Kelvin probe force microscopy, and ultraviolet photoelectron spectra measurements. The down-shifts of work functions lead to a decreased level of potential energy and hence increased V oc of the PSC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
1
35
0
3
Order By: Relevance
“…transporting layer (ETL) or hole transporting layer (HTL); [182,183] Liu et al used aZ nO@C 60 bilayer as the ETL and NiO as the HTL in an inverted cell which demonstrated high electron extraction efficiency and low leakage loss. [76] Theresulting cell yielded asPCE of around 12 %and rfV OC = 1.09 V. Yane tal.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…transporting layer (ETL) or hole transporting layer (HTL); [182,183] Liu et al used aZ nO@C 60 bilayer as the ETL and NiO as the HTL in an inverted cell which demonstrated high electron extraction efficiency and low leakage loss. [76] Theresulting cell yielded asPCE of around 12 %and rfV OC = 1.09 V. Yane tal.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…[1d] So far, there have been a large number of efforts devoted to obtaining effective surface trap passivation through incorporating interlayers in PSCs with p‐i‐n or n‐i‐p device structures. For HTLs, in addition to inorganic materials (NiO x , CuSCN, MoO x , etc. ), organic counterparts of both small molecules and polymers have been widely used in PSCs with tunable work functions and surface properties.…”
Section: Interface Modification For Pscsmentioning
confidence: 99%
“…Graphene‐based materials have been used as modifiers in ETLs and HTLs, but they have also been directly utilized as CTLs in planar PSCs. [ 135,136 ] Research articles on the direct utilization of graphene as ETL are hardly reported in the regular planar PSCs, whereas there are many important research works on the direct utilization of graphene as HTL in inverted planar PSCs. This can be attributed to the reason that the Fermi level of graphene is close to the valence band of perovskite, so graphene films are more suitable for hole extraction.…”
Section: Application Of Graphene In Each Layer Of Planar Pscsmentioning
confidence: 99%